Draft Annual Plan (2003-04) Administration of Union Territory of Dadra and Nagar Haveli - Planning Commission (Planning Commission, 2003)
The Union Territory of Dadra and Nagar Haveli is situated on the Western Coast of India between the parallels of 20° -0° and 20° -25° of latitude north and between the meridian 72° -50° and 73° -15° of longitude east. Its (provisional ) population as per 2001 Census is 2,20,451 (1,21,731 male and 98,720 females). It has an area of 491 sq.km, and comprises two enclaves viz; (1) Dadra and (2) Nagar Haveli, having 72 villages. Silvassa, the capital of this U.T. and its adjoining village Amli have been treated as non-statutory Census Town. The territory is surrounded by Valsad District of Gujarat and Thana District of Maharashtra.
Union Territory of Dadra and Nagar Haveli, Department of Planning and Statistics